Up, up, and away : the story of Amelia Earhart - Canizares, Susan (New York : Scholastic, 2003)
Take off on a journey with Amelia Earhart, one of America's most famous pilots.
Keywords: Amelia Earhart -- Biography; Pilot -- Juvenile literature